2019
DOI: 10.1186/s41239-019-0172-z
|View full text |Cite
|
Sign up to set email alerts
|

Using learning analytics to develop early-warning system for at-risk students

Abstract: In the current study interaction data of students in an online learning setting was used to research whether the academic performance of students at the end of term could be predicted in the earlier weeks. The study was carried out with 76 secondyear university students registered in a Computer Hardware course. The study aimed to answer two principle questions: which algorithms and features best predict the end of term academic performance of students by comparing different classification algorithms and pre-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
100
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(105 citation statements)
references
References 15 publications
1
100
0
4
Order By: Relevance
“…IG(S, a) = H(S)-H(S|a) (10) where, IG(S, a) is the dataset S information for the variable a for a random variable, H(S) is the entropy for the dataset before any adjustment and H(S | a) is the conditional entropy for the variable given a. Table 6 shows the important features that support the classification results arranged from the higher ratio to the lower.…”
Section: Results Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IG(S, a) = H(S)-H(S|a) (10) where, IG(S, a) is the dataset S information for the variable a for a random variable, H(S) is the entropy for the dataset before any adjustment and H(S | a) is the conditional entropy for the variable given a. Table 6 shows the important features that support the classification results arranged from the higher ratio to the lower.…”
Section: Results Discussionmentioning
confidence: 99%
“…Akçapınar et al [10] the authors used learning analytics to develop an early warning system for at-risk students. They used in the implementation of their research experiment the Orange data mining tool.…”
Section: Introductionmentioning
confidence: 99%
“…Interventions at this stage can be effective in preventing students' possible failures. Studies demonstrate that the students' end-of-year performances can be predicted accurately from the first weeks of the course (Akçapınar, Altun, & Aşkar, 2019). It is fundamental to design and test interventions especially for students who are likely to fail the course in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The regression model that emerged as a result of the analysis shows that the interaction data reflecting the students' online learning behavior can markedly predict 70% of the variance in learning performance. Moreover, in another study, an early warning system is developed to estimate the academic performance of the at-risk students by using learning analytics data in a Computer Hardware course conducted through blended learning (Akçapınar, Altun, & Aşkar, 2019). As a result of the study in which different classification algorithms are put to work; It is revealed that the prediction models created based on the interaction data of the students can predict the students who are going to fail in the third week of the course.…”
Section: Online Learning Experiences In Terms Of Blended Learningmentioning
confidence: 99%
“…The prediction of student academic performance helps in identifying weak students who will struggle with their studies. Science and IT majors are among the hardest at college level [1], [2]. Therefore, the management of computer and IT related institutions take essential steps to detect and correct the way for weak students.…”
Section: Introductionmentioning
confidence: 99%